Penyembuhan Rohani dan Pemulihan Identitas : Pendekatan Hermeneutika terhadap Kisah Pertobatan Paulus di Kisah Para Rasul 9:17 - Surudiaman Lase; Iman Pasrah Zai; Malik Bambangan (LPPM - STT Kadesi Bogor, 2025)
In this article, we use a hermeneutical approach to look at the concepts of spiritual healing and identity restoration in the context of Christian life. It looks at Paul's conversion from a persecutor of the church to a servant of Christ, where he discovers his true identity in Christ through a deep spiritual encounter. these topics in the modern Christian life, where many people seek spiritual healing and identity restoration in a world that is full of pressure and confusion. Everyone who is a Christian is called to experience a transformation through repentance and receiving the Holy Spirit, which allows them to live with divine purpose and recognize who they truly are before God.